Feed additives for swine: Fact sheets – prebiotics and probiotics, and phytogenics - Jacela, J.Y.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Renter, David G.; Dritz, Steven S. (My University, 2013)
There is increasing pressure for livestock producers to minimize the use of antibiotics as growth promoters in food animals. Supplementing beneficial microorganisms in the gastrointestinal tract is one potential alternative. A diverse population of beneficial and potentially harmful microorganisms exists in the gastrointestinal tract of the pig. In a healthy animal, a delicate balance between these two groups of organisms is maintained. However, during times of stress, such as during weaning in the case of piglets, this balance may be affected and can lead to a rapid growth of harmful microorganisms. This may result in poor performance or disease. Thus, prebiotics and probiotics have been the subject of much research over the years as potential replacements for antibiotic growth promoters in pigs.
Keywords: Swine; Feed additives; Prebiotics; Probiotics; Phytogenics; Growth; Growth performance